2004
DOI: 10.1534/genetics.103.024851
|View full text |Cite
|
Sign up to set email alerts
|

The Origin Recognition Complex Links Replication, Sister Chromatid Cohesion and Transcriptional Silencing in Saccharomyces cerevisiae

Abstract: Mutations in genes encoding the origin recognition complex (ORC) of Saccharomyces cerevisiae affect initiation of DNA replication and transcriptional repression at the silent mating-type loci. To explore the function of ORC in more detail, a screen for genetic interactions was undertaken using large-scale synthetic lethal analysis. Combination of orc2-1 and orc5-1 alleles with the complete set of haploid deletion mutants revealed synthetic lethal/sick phenotypes with genes involved in DNA replication, chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
107
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 72 publications
11
107
0
1
Order By: Relevance
“…Loss of cohesion is essential to establish silencing at HMR, while loss of the Mcd1/Scc1 cohesin subunit allows silencing to be established prematurely (Lau et al 2002). In contrast, it was also observed that DNA replication factors needed to establish cohesion are also required for silencing at telomeres and the mating-type loci (Suter et al 2004). In these cases, it is unclear if the effects of cohesin are as direct as they appear to be in the case of its function at the HMR boundaries.…”
Section: Cohesin and Yeast Gene Silencingmentioning
confidence: 99%
“…Loss of cohesion is essential to establish silencing at HMR, while loss of the Mcd1/Scc1 cohesin subunit allows silencing to be established prematurely (Lau et al 2002). In contrast, it was also observed that DNA replication factors needed to establish cohesion are also required for silencing at telomeres and the mating-type loci (Suter et al 2004). In these cases, it is unclear if the effects of cohesin are as direct as they appear to be in the case of its function at the HMR boundaries.…”
Section: Cohesin and Yeast Gene Silencingmentioning
confidence: 99%
“…Hence, silencing of the telomeres is mediated by similar, but not identical mechanisms to these employed at the mating loci. The growing list of factors engaged in silencing also includes the histone acetyl transferase NuA4 (Babiarz et al 2006;Clarke et al 2006), the histone chaperone CAF-1 (Tamburini et al 2006), cohesin (Suter et al 2004;Chang et al 2005), SUM1 (Irlbacher et al 2005), and SCP160 (Marsellach et al 2006).…”
mentioning
confidence: 99%
“…Furthermore, robust silencing at HMR does not take place until M-phase (Lau et al 2002). Nevertheless, many of the genes that affect silencing both at telomeres and at HM loci encode for bona fide DNA replication factors such as ORC2, ORC5, minichromosome maintenance (MCM)5, MCM10, CDC44(RF-C), CDC45, and POL30(PCNA) (Ehrenhofer-Murray et al 1995Dillin and Rine 1997;Fox et al 1997;Dziak et al 2003;Suter et al 2004;Liachko and Tye 2005).…”
mentioning
confidence: 99%
“…The chromatids remain paired until the transition from the metaphase to anaphase, when the contacts between them break and chromatids are pulled to the opposite poles of the cell [64]. Genetic studies have found that ORC mutations in yeast ( orc2–1 and orc5–1 ) and in Drosophila ( orc6) cause numerous cell cycle defects, including mitotic defects [65,66]. Mutational analyses in yeast revealed interactions between the ORC genes and the genes of proteins responsible for the sister chromatid cohesion.…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%
“…Mutational analyses in yeast revealed interactions between the ORC genes and the genes of proteins responsible for the sister chromatid cohesion. Double mutants showed an enhanced impairment of sister chromatid cohesion, which suggested an involvement of ORC in this process [65]. However, whether ORC plays a direct role in sister chromatid cohesion or the observed effects are the consequence of a replication impairment remained for a long time unclear.…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%